KAJIAN DIMENSI SALURAN PRIMER EKSISTING DAERAH IRIGASI SUNGAI TANANG KABUPATEN KAMPAR - Djuang Panjaitan; SH Hasibuan (Jurnal APTEK, 2011)
The aim of this research was analyze of existing primary canal dimension at Sungai Tanang Irrigation Area, Kampar District in order courage program of Operasi Pangan Riau Makmur (OPRM) Riau Province for empowerment of rice. Method was used to analyze the water available using Mock Method by rainfall data in Pasar Kampar Station at year 1998 to 2008, and so climate data such as temperature, wind speed, humidity and sunshine. For the analyze of discharge capacity primary canal at Sungai Tanang Irrigation Area, Kampar District using Continuity Law formulation. The result of this research prove that condition of capacity discharge for existing primary canal at Sungai Tanang Irrigation area 0.09 m3/sec still have ability to the planting pattern scenario pady-pady-pady, the maximum irrigation water requirment were found on May 0.03 m3/sec.